2023
DOI: 10.3390/foods12071428
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Alcoholic Fatty Liver by Dendrobium officinale Flower Extracts due to Regulation of Gut Microbiota and Short-Chain Fatty Acids in Mice Exposed to Chronic Alcohol

Abstract: Alcoholic fatty liver disease (AFLD) is caused by long-term heavy alcohol consumption; therefore, useful and practical methods for the prevention of AFLD are urgently needed. The edible flower of Dendrobium officinale contains diverse flavonoids, and has shown antioxidant activity as well as antihypertensive and anti-inflammatory effects. In this study, an AFLD model was established, the protective effect of D. officinale flower (DOF) ethanol extract on AFLD was evaluated, and its mechanisms were investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Previous studies have demonstrated that the addition of bile salts or bile acid analogs to food can impact the composition of the intestinal microbiota, the predominant producers of short-chain fatty acids in the intestinal environment are Bacteroidota and Firmicutes. [42][43][44] Recent studies have reported that the gallstone group is characterized by a decreased abundance of Firmicutes and Spirochaetia, alongside an increase in Bacteroidota, Deferribacteres, and Proteobacteria. 45,46) In our study, we found that a high-fat diet compromises the diversity of the gut microbiota in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the addition of bile salts or bile acid analogs to food can impact the composition of the intestinal microbiota, the predominant producers of short-chain fatty acids in the intestinal environment are Bacteroidota and Firmicutes. [42][43][44] Recent studies have reported that the gallstone group is characterized by a decreased abundance of Firmicutes and Spirochaetia, alongside an increase in Bacteroidota, Deferribacteres, and Proteobacteria. 45,46) In our study, we found that a high-fat diet compromises the diversity of the gut microbiota in mice.…”
Section: Discussionmentioning
confidence: 99%
“…officinale flower (Zhang et al, 2023), modified cereal bran (Devi et al, 2023), and some other nutraceutical foods also could promote the growth of A. muciniphila and the production of SCFAs to exert their protection effect on human health. These studies indicated that the effectiveness of functional foods or medicinal foods relies, to some extent, on the enrichment of A. muciniphila and its related metabolite SCFAs.…”
Section: Short-chain Fatty Acids (Scfas)mentioning
confidence: 99%
“…The hepatoprotective potential of food is presented in Table 1. Alcohol, being a highly toxic and carcinogenic substance, is considered a factor contributing to liver inflammation and fibrosis [103]. A literature review indicates the necessity for individuals with non-alcoholic fatty liver disease to abstain from alcohol consumption, because of a proven reduction in HCC risk in this group [104].…”
Section: Interesting Potential Of Mushrooms In Hcc Prevention and Tre...mentioning
confidence: 99%